International Handbook of Foodborne Pathogens - Miliotis, Marianne D;Ed. Bier, Jeffrey W;Ed (Food Science and Technology (Marcel Dekker, Inc.), 125., 2003)
Describes the management, control, and prevention of microbial foodborne disease. This handbook analyzes transformations in the epidemiology of foodborne disease from increased transnational food exchange to examinations of various zoonoses. It discusses the prevalence and risk of foodborne disease in developing and industrialized countries.